Significant control of metal-insulator transition temperature through catalytic excessive oxygen doping in high-performance vanadium dioxide nanobeam channel - Ko, Minhwan; Lee, Sang Yeon; Park, Jucheol; Seo, Hyungtak (Journal of Materials Science and Technology, 2020)
The strategy of a reliable transition temperature control of vanadium dioxide (VO2) is reported. Rectangular VO2 nanobeams were synthesized by a thermal chemical vapor deposition (TCVD) system. The metal-insulator transition (MIT) temperature increases to above 380 K when the TiO2 ratio of the source is 5 at.%, although the Ti source is not physically doped into VO2 nanobeams. The XPS spectra of the V 2p orbital reveal the excessive oxidation of V after the TCVD processes with a higher TiO2 ratio, indicating that the TiO2 precursor is important in the O-doping of the surface V[sbnd]O bonds when forming volatile Ti-O gas species. Thus, TiO2 reactants can be used as a VO2 surface chemical modifier to manipulate the MIT transition temperature and maintain a homogenous VO2 phase, which is useful for a Mott device application with a record on/off switching ratio > 104 and Mott transition temperature > 380 K.
Keywords: Device application; Gas species; Mott transitions; Oxygen doping; Surface chemicals; Temperature increase; Thermal chemical vapor deposition; Titanium catalyst; Metal–insulator transition temperature; Mott transition; Oxygen doping; Titanium catalyst; VO2